The association between presenting complaints and clinical outcomes in emergency department patients of different age categories. (February 2022) - Raven, Wouter; van den Hoven, Elisa M.P.; Gaakeer, Menno I.; Ter Avest, Ewoud; Sir, Ozcan; Lameijer, Heleen; Hessels, Roger A.P.A.; Reijnen, Resi; van Zwet, Erik; de Jonge, Evert; Nickel, Christian H.; de Groot, Bas
Abstract : Background and importance: Although aging societies in Western Europe use presenting complaints (PCs) in emergency departments (EDs) triage systems to determine the urgency and severity of the care demand, it is unclear whether their prognostic value is age-dependent. Objective: To assess the frequency and association of PCs with hospitalization and mortality across age categories. Methods: An observational multicenter study using all consecutive visits of three EDs in the Netherlands Emergency department Evaluation Database. Patients were stratified by age category (0–18; 19–50; 51–65; 66–80; >80 years), in which the association between PCs and case-mix adjusted hospitalization and mortality was studied using multivariable logistic regression analysis (adjusting for demographics, hospital, disease severity, comorbidity and other PCs) Results: We included 172  104 ED-visits. The most frequent PCs were 'extremity problems' [range across age categories (13.5–40.8%)], 'feeling unwell' (9.5–23.4%), 'abdominal pain' (6.0–13.9%), 'dyspnea' (4.5–13.3%) and 'chest pain' (0.6–10.7%). For most PCs, the observed and the case-mix-adjusted odds for hospitalization and mortality increased the higher the age category. The most common PCs with the highest adjusted odds ratios (AORs, 95% CI) for hospitalization were 'diarrhea and vomiting' [2.30 (2.02–2.62)] and 'feeling unwell' [1.60 (1.48–1.73)]. Low hospitalization risk was found for 'chest pain' [0.58 (0.53–0.63)] and 'palpitations' [0.64 (0.58–0.71)]. Conclusions: Frequency of PCs in ED patients varies with age, but the same PCs occur in all age categories. For most PCs, (case-mix adjusted) hospitalization and mortality vary across age categories. 'Chest pain' and 'palpitations, ' usually triaged 'very urgent', carry a low risk for hospitalization and mortality. Abstract : Supplemental Digital Content is available in the text.